Exploration of the Operating Room Personnel From Components and Examples of Interprofessional Collaboration: A Phenomenological Study - Mitra Amini (Qom University of Medical Sciences, 2021)
Background and Objectives: Inter-professional collaboration is one of the most important components of patient safety.Understanding the components of interprofessional collaboration is essential. So far, few studies have been conducted on interprofessional cooperation in the operating room, worldwide and in Iran.The aim of this study was to explain the experiences of operating room staff from the components and examples of interprofessional collaboration using the phenomenological approach by Colaizzi method (1978). The aim of this study was to explain the experiences of operating room staff from the components and examples of interprofessional collaboration using the phenomenological approach by Colaizzi method (1978). The aim of this study was to explain the experiences of operating room staff from the components and examples of interprofessional collaboration using the phenomenological approach Colaizzi method (1978). Methods: 12 employees working in different professions in the operating room of Qom hospitals were included.The study was conducted in a qualitative phenomenological manner with the Colaizzi method and structured goal-based interviews. Results: From the analysis of the obtained data, 6 Emergent Them and 20 Theme Clusters were obtained as follows: “Organization” (goal setting and shared resources), “Professional Identity” (commitment,mutual‏respect, synergy‏ and clear role), ”Communication”  (Collaboration, Trust, Information Sharing, and Conflict Management “Team Characteristics (Flexibility, Experience, Participation, Teamwork, and responsibility،accountability)”, Leadership and Management (Operating Room Leadership, Hierarchy Structure, Climate, Working Conditions, and Capacity)  “Coordination” (planning) Conclusion: Staff training and explaining the experience of  other operating room staff about the components of Inter-professional collaboration, could be considered as one of the main steps to achieve inter- Inter-professional collaboration and patient safety. The results of this study can  be helpful education officials in improving and improving the quality of joint inter-professional training programs.